28. PENUNDAAN INDONESIA DALAM MERATIFIKASI PERJANJIAN EKSTRADISI DENGAN SINGAPURA TAHUN 2007-2014 (STUDI KASUS: KORUPSI BLBI) - Wicaksana, Avinasa Suryagilang; Susiatiningsih, Hermini; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Indonesia is one of the country with a high level of corruption. One issue that stands out isBLBI (Bank Indonesia Liquidity Assistance). This problem then developed to complexwhen the suspects fled to neighboring countries, namely Singapore. To overcome this, in2007 Indonesia - Singapore conclude an extradition treaty. But after that Indonesia delaythe extradition treaty, because Singapore input this agreement in DCA (DefenseCooperation Agreement). By using the theory of realism and globalization to see thatthreatened state security and corruption offenses be transnational crime, as well asqualitative methods, this study analyzes why Indonesia postponed the extradition treatybetween Indonesia and Singapore 2007-2014, particularly in cases of corruption. The studyfound that although the delays Indonesia to ratify the extradition treaty, which leads to thedifficulties of law enforcement for criminals who flee to Singapore, Indonesia will remainin his stance by not ratifying the extradition. This is because Indonesia will experience alot of harm, such as threats to the